Quranic evaluation of CEDAW’s reproductive rights - Ahmad, Nadzrah; Ismail, Nurul Syuhada; Zakariyah, Luqman; Wan Yusoff, Wan Mazwati (AESS Publications, 2019)
Over the last few decades, reproductive issues have never been the center of attention. However, recently, there has been a women‟s movement formed to champion women‟s rights and counter the issue of women being equated to reproduction and having no say or rights to choose in this matter. Today, the Convention on the Elimination of all Forms of Discrimination against Women (CEDAW), as an international bill of women‟s rights, demands for all countries to accord to and recognize women‟s reproductive rights, which includes the right to abortion. In contrast, the Quran, which is a major source of Muslim rules and practices, interprets that the rights are contrary to CEDAW, as the rights are not disseminated solely for women. This article will focus on the contradiction between the dissemination of reproductive rights and its interpretation. CEDAW‟s approach will be evaluated through Quranic interpretations. This study will adopt a qualitative methodology which examines Quranic interpretations and CEDAW‟s reproductive rights. The study also demonstrates that Quranic interpretations and disseminations are comprehensive and that the rights are not solely granted to women as several aspects of life are concerned. In contrast, CEDAW stands for reproductive freedom and self-determination solely given to women.